Effect of different silviculture treatments on growth performance of Kapur Bukit (Dryobalanops beccarii) at Gunung Apeng Forest Reserve, Sarawak - Zatil Aisyah, Zainudin (2015)
A study on the effect of different silviculture treatments towards 10, 9, 8 and 7 years-old of Kapur Bukit (Dryobalanops beccarii Dyer, J. Bot) was planted as enrichment planting in Gunung Apeng Forest Reserve, Sarawak. Silvicultre treatments that have been applied to the plots were (i) line slashing (T1), (ii) girdling and line slashing (T2) and (iii) control (T3). The objectives of this study were to evaluate the growth performance of Dryobalanops becarii planted under the canopy of secondary pioneer species using line planting technique. Besides that, this study help in determined the response of prescribed silviculture treatment on the growth of Dryobalanops becarii of different age group. A 50m x 100m plot was established at each site of the 2005 (DB05), 2006 (DB06), 2007 (DB07) and 2008 (DB08) plot of D. Beccarii Dyer. The plot was further divided into 6 subplots with 30 trees each. The growth performance of different age stand of planted D. Beccarii was evaluated on the total tree height, tree diameter and relative growth rate. Initially, plots DB05 & DB06 had survivability of 75.5% and 77.2 %. Whereas, DB07 had survivability of 87.25% higher than DB08 (60.6%). After silviculture treatment applied, plot DB05 & DB08 decreased to 75.0% and 55.6% respectively. For plot DB06 and plot DB07 remain the same. Between T1, T2 & T3, T2 area showed a lower number of mortality in plot DB05 & DB07. Whereas, in plot DB06 & DB08 a lower mortality showed by T1 area. The initial mean tree height of DB05 plot was 4.77m ± 1.75. Plot DB06 showed a mean tree height of 3.68m ± 1.60. While plot DB07 had a mean tree height of 2.44m ± 1.37and plot DB08 had a mean tree height 1.88m ± 0.81. After 16 months of treatment, plot DB05 had the tallest tree among other plots with a height of 6.51m ± 2.05.